Redesigning the Concept of Law Enforcement in Administrative Violations of General Elections in Indonesia - Jamil, Jamil; Fadli, Moh.; Hadiyantina, Shinta; Prasetyo, Ngesti Dwi (Universitas Airlangga, 2024)
Trial mechanism as the only procedure in resolving election administrative violations is a mechanism that is not in accordance with the concept of law enforcement in administrative law that uses not only the trial mechanism but also direct sanctions. Therefore, the concept of law enforcement in these violations needs to be redesigned, to be in line with the administrative law and be more effective and easier to implement. This study examined the concept of law enforcement in administrative law as a conceptual and theoretical basis in redesigning the concept of law enforcement in election administrative violations. It used legal research methods with statutory, conceptual, and comparative approaches. The results of this study recommend a new concept in resolving election administrative violations by looking at the legal subjects who commit violations and the characteristics of the violations. For the violations committed by non-officials, the law enforcement is sufficient to use direct sanctions. Meanwhile, for the violations committed by officials, if they cause direct losses, it must use a trial mechanism. But, if the violation is only limited to non-compliance with the legislation and does not cause harm to anyone, direct sanctions can be executed. Hence, it is necessary to change the mechanism for resolving election administrative violations as stipulated in the Election Law.